PERAN MEDIA DALAM MEMBANGUN OPINI PUBLIK TENTANG KERUSUHAN TASIKMALAYA 1996 - Anggi A Junaedi (Sinau : Jurnal Ilmu Pendidikan dan Humaniora, 2021)
The Tasikmalaya incident was a major and historic event that occurred in 1996. As a major event, media such as newspapers will never forget to report it. Interestingly, each newspaper has its own perspective in seeing reality. This method is used by media in a reality to then be constructed and produced in the form of news. As a result, the production of news varies even if the object is the same, whether we realize it or not. In the world of the press, this activity is known as media politics. And also, a historical event by Fernand Braudel declared as a historical event in a quick period of time. It is interesting to study how the media with Islamic and nationalist ideology reported on the Tasikmalaya incident because the incident involved these two elements. To answer this problem, the historical method is used which begins with a heuristic process, criticism, enters the interpretation process and historiography activities at the end. As a result, the construction of the news carried out by the Islamic and nationalist newspapers was very different. Ideology does influence the news. However, ownership and environmental factors cannot be ignored. Even more influential than ideology. In reporting Tasikmalaya, Islamic newspapers tend to defend Muslims. Meanwhile nationalist newspapers blame Muslims.